Preorganizing linear (self-complementary) quadruple hydrogen-bonding arrays using intramolecular hydrogen bonding as the sole force - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2005)
In this article we describe a rational approach for prefixing multiple cooperative binding sites in an ideal spatial arrangement on a structurally rigid backbone, constrained exclusively by intramolecular hydrogen bonding. The idea is exemplified by the ability of the self-assembling constructs la-e and 2a,b to form hydrogen-bonded dimers, whose structural preorganization has been solely effected by intramolecular hydrogen bonding. The readily accessible amidinourea backbone has been used as a common platform for the construction of a variety of such self-assembling systems. ESI mass spectrometry and single-crystal X-ray diffraction studies have been particularly effective in investigating the self-assembling propensities of these systems. Remarkably, most the H-bonded dimers reported herein undergo an unusual mode of self-assembly, using intermolecular four-membered ring hydrogen-bonded interaction, affording extended supramolecular networks.

Hybrid foldamer with unique architecture from conformationally constrained aliphatic-aromatic amino acid conjugate - Srinivas, Deekonda; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Tetrahedron, 2006)
In this paper, we describe the design and synthesis of a novel hybrid foldamer, derived from a conformationally constrained aliphatic-aromatic amino acid conjugate that adopts a well-defined, compact, three-dimensional structure, governed by a combined conformational restriction imposed by the individual amino acids from which the foldamer is composed. Conformational investigations confirmed the prevalence of a unique doubly bent conformation for the foldamer, in both solid and solution states, as evidenced from single crystal X-ray and 2D NOESY studies, respectively. The findings suggest that constrained aliphatic-aromatic amino acid conjugates offer new avenues for the de novo design of hybrid foldamers with distinctive structural architectures. Furthermore, the de novo design strategy disclosed herein has the potential for significantly augmenting the `tool-box' of the modern day peptidominetic chemist, as well as providing a novel approach to the field of rational design. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Conformation; Foldamer; Peptidomimetics

Synthesis of 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans relationships - Edwards, Alison A.; Sanjayan, Gangadhar J.; Hachisu, Shuji; Soengas, Raquel; Stewart, Alistair; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Templated tetrahydrofuran-based gamma-azido esters were prepared with the C-2 and C-4 functionalities in cis and trans relative configurations. This was achieved by ring contraction of the suitably protected 2-O-triflates of pentono-1,5-lactones (D-ribose and L-arabinose) with subsequent introduction of the azide via the 4-O-triflate. Access to a corresponding beta-azido ester was achieved in good yield. Little elimination product was observed by introduction of the azide via the 3-O-triflate. These azido esters are scaffolds. which may be predisposed to adopt secondary structural motifs, for example. for use as peptidomimetics; they may also be utilised for the preparation of stereodiverse compound libraries. (c) 2006 Elsevier Ltd All rights reserved.
Keywords: gamma amino acids; Peptidomimetics; scaffolds; sugar amino acids

Enantioselective syntheses of (-)-pinellic acid, alpha- and beta-dimorphecolic acid - Baruah, Pranjal K.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Tetrahedron, 2007)
An efficient enantioselective convergent approach for the synthesis of (-)-pinellic acid 1, alpha- and beta- dimorphecolic acid (2 and 3) from 1,9-nonane diol is described. The synthetic strategy features Sharpless asymmetric hydroxylation, Sonogashira coupling and Birch reduction. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric dihydroxylation; influenza; Sonogashira coupling

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

N,N `,N `'-Tri-Boc-guanidine (TBG): a common starting material for both N-alkyl guanidines and amidinoureas - Prabhakaran, Panchami; Sanjayan, Gangadhar J. (Tetrahedron Letter, 2007)
{In this Letter, we describe the unexpected reaction pattern of N,N',N''
Keywords: 1-substituted-1H-1; 2; 3; 4-tetrazoles; Ionic liquid; sodium azide; substituted amine; triethyl orthoformate

Di-tert-butyl N,N `-(octahydropentalene-2,5-diyl) dicarbamate - Kendhale, Amol M.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2008)
In the molecule of the title compound, C18H32N2O4, the central bicyclo[3.3.0] octane (octahydropentalene) has a rigid ring junction. Both rings of the bicyclo[3.3.0] octane unit adopt an envelope conformation, and the flexible tert-butylcarbamoyl side chains each have an extended conformation. Such a constrained bicyclo[3.3.0] octane aliphatic template is of interest with respect to the design of novel self-assembling motifs. Molecules related by c-glide symmetry are linked via intermolecular N-H center dot center dot center dot O hydrogen bonds, forming a two-dimensional layer structure. Neighboring layers are weakly associated along the a axis due to the close approach of the tert-butylcarbamoyl groups (2.55 angstrom).

Foldamers with unusual structural architecture from spirobi(indane) building blocks - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
This communication demonstrates the utility of inherently rigid building blocks such as 1,1'-spirobi(indane) for generating conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Pre-organization-mediated macrocylization: efficient synthesis and structural investigations of BINOL-m-phenylenediamine-derived macrocycles - Srinivas, Deekonda; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This letter describes a serendipitous discovery of an efficient synthetic route to BINOL-m-phenylenediamine-derived macrocycles. These macrocycles are quickly accessible in an one-pot procedure by the direct condensation of (R) and (S) BINOL bis-acids with suitably substituted m-phenylenediamine analogs. Structural investigations by single crystal X-ray crystallography and solution-state NMR studies provided convincing evidence of their intramolecular hydrogen bonding arrangement and rigid structural architecture. The striking feature of these macrocycles is their ready accessibility in optically pure form coupled with their ease of synthesis. (C) 2008 Elsevier Ltd. All rights reserved.

Rigid bicyclo[3.3.0]octane (octahydropentalene): a heavily constrained novel aliphatic template for molecular self-assembly - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This Letter reports the utility of a heavily constrained cis-fused bicyclo[3.3.0]octane (octahydropentalene) aliphatic template for effecting molecular self-assembly. An attractive feature of this system is its heavily constrained alicyclic backbone that would allow for the exploration of self-assembling systems with conformationally ordered features. (C) 2008 Elsevier Ltd. All rights reserved.

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Tandem non-polymerizing strategy to higher order acrylamide oligomers; potential intermediates for conformational correlations of poly-N-acrylamides - Kendhale, Amol M.; Rajamohanan, Pattuparampil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2008)
This letter describes an efficient tandem non-polymerization strategy to deliver higher order N-acrylamide oligomers. These oligomers, accessible in an one-pot procedure, are potential intermediates for the correlation of stereochemistry (tacticity) with conformation and hydrogen bonding propensities in poly (oligo) N-acrylamides.

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

1,8-Bis(4-methoxy-3-nitrophenyl)naphthalene - Prabhakaran, Panchami; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Acta Crystallographica Section E-Structure Reports Online, 2011)
Molecules of the title compound, C(24)H(18)N(2)O(6), are located on a twofold rotation axis passing through through the central C-C bond of the naphthalene ring system. The molecular conformation is characterized by a roughly coplanar arrangement of the two substituted phenyl rings [dihedral angle 18.53 (5)degrees]. These two aryl rings are each twisted by 65.40 (5)degrees from the plane of the naphthyl unit.

Bicyclic amino acid-carbohydrate-conjugates as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres - Kale, Sangram S.; Chavan, Sanjay T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes a general synthetic route to bicyclic amino acid-carbohydrate-conjugates, which would be useful as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres. The synthesis was achieved in 12 steps starting from D-glucose. The striking features of this system are the bicyclic rigid core displaying an a-amino acid side chain and hydroxyethylamine moiety - both of which would be potentially important for receptor interactions, leading to various biomedical responses, as described in the literature. Crystal structure investigation suggested extensive intermolecular hydrogen-bonding interactions in this system, involving the backbone amide and hydroxyl groups.

Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Diversifying the structural architecture of synthetic oligomers: the hetero foldamer approach - Roy, Arup; Prabhakaran, Panchami; Baruah, Pranjal Kumar; Sanjayan, Gangadhar J. (Chemical Communications, 2011)
Conformationally ordered synthetic oligomers, also called ``foldamers'', have attracted considerable attention in recent years owing to their ability to mimic the structural architecture of biopolymers and also because of their potential applications in biomedical and material science fields. Until recently, the major focus in this area has been the development of oligomers featuring a single type of monomer building blocks. However, due to the enormous possibility of augmenting the conformational space available for oligomer design, the hetero foldamer approach has been introduced very recently. This feature article aims to describe foldamers with unique structural architectures, exclusively featuring heterogeneous backbones (hetero foldamers).

Carbohydrate-derived conformationally restricted bicyclic dipeptides as potential hetero foldamer building blocks - Ramesh, Veera V. E.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Tetrahedron-Asymmetry, 2012)
Starting from carbohydrate precursors, hetero foldamer building blocks featuring diverse amino acid side chains and stereochemistry have been accessed via a multi-step synthetic protocol. These conformationally restricted bicyclic dipeptide building blocks are characterized by a constrained beta-lactam ring fused with a pyrrolidine ring carrying a hydroxyethylamine isostere (HEA) on the backbone. These building blocks offer the possibility of developing foldamers with interesting structural architectures, conspicuously different from those classically observed. Furthermore, such hetero-building blocks have the potential to augment the conformational space available for foldamer design with diverse backbone conformations and structural architectures. (C) 2012 Elsevier Ltd. All rights reserved.

Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers

Foldamers: they're not just for biomedical applications anymore - Prabhakaran, Panchami; Priya, Gowri; Sanjayan, Gangadhar J. (Angewandte Chemie-International Edition, 2012)
Keywords: Foldamers; foldaxanes; molecular shuttles; nanotechnology

Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.

Sugar-amino acid cyclic conjugates as novel conformationally constrained hydroxyethylamine transition-state isosteres - Roy, Arup; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2012)
Hydroxyethylamine (HEA) isosteres have previously been shown to display a multitude of biomedical applications. In fact, the first protease inhibitor, saquinavir is an HEA based peptidomimetic. Herein we describe an easy-to-operate synthetic route to a series of carbohydrate-based conformationally constrained hydroxyethylamine (HEA) isosteres featuring amino acid side chains, starting from D-glucose. This class of novel sugar-amino acid-tethered conformationally restricted HEA systems may have bearing in practical application, particularly in the development of conformationally restricted protease inhibitors. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Conformationally constrained; D-Glucose; hydroxyethylamine isosteres; protease inhibitor; Reductive amination

Unusual conformational similarity of two peptide folds featuring sulfonamide and carboxamide on the backbone - Vijayadas, Kuruppanthara N.; Davis, Hilda C.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Two folded peptides featuring carboxamide and sulfonamide at the core of the peptide fold have been shown to possess almost similar conformational features, despite the well-known fact that carboxamides and sulfonamides have strikingly different hydrogen-bonding and geometrical preferences.

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Easy and multigram-scale synthesis of pillar[5]quinone by the hypervalent iodine oxidation of 1,4-dimethoxypillar[5]arene - Shivakumar, Kilingaru I.; Sanjayan, Gangadhar J. (Synthesis-Stuttgart, 2013)
Pillar[5]quinone (P[5]Q), a potential molecule for anion recognition and supramolecular host-guest chemistry, has not as yet been used for practical purposes, presumably due to the synthetic difficulties in obtaining it in large amounts. Herein, we reveal an easy-to-operate and chromatography-free synthetic strategy that can furnish P[5]Q on a multigram scale; its success relies on the utility of hypervalent iodine, generated in situ from Oxone/ iodobenzene, as an efficient oxidant. Pillar[5]quinone was obtained in multigram quantities by oxidation of 1,4-dimethoxypillar[5]arene with Oxone/iodobenzene and simple purification by crystallization from 1,1,2,2-tetrachloroethane, thus opening up the opportunity to explore the properties of this interesting macrocyclic quinone.
Keywords: hypervalent iodine oxidation; macromolecules; pillar-arenes; supramolecular chemistry

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Orthanilic acid-promoted reverse turn formation in peptides - Kale, Sangram S.; Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2013)
Orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant), an aromatic beta-amino acid, has been shown to be highly useful in inducing a folded conformation in peptides. When incorporated into peptide sequences (Xaa-(S)Ant-Yaa), this rigid aromatic beta-amino acid strongly imparts a reverse-turn conformation to the peptide backbone, featuring robust 11-membered-ring hydrogen-bonding.

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Conformational modulation of peptide secondary structures using beta-aminobenzenesulfonic acid - Kale, Sangram S.; Kunjir, Shrikant M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
This communication describes the influence of beta-aminobenzenesulfonic acid ((S)Ant) on the conformational preferences of hetero foldamers. The designed (Aib-(S)Ant-Aib)(n) and (Aib-(S)Ant-Pro)(n) oligomers display a well-defined folded conformation featuring intramolecular mixed hydrogen bonding (7/11) and intra-residual (6/5) H-bonding interactions, respectively.

Formation of a pseudo-beta-hairpin motif utilizing the Ant-Pro reverse turn: consequences of stereochemical reordering - Nair, Roshna V.; Kotmale, Amol S.; Dhokale, Snehal A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2014)
Herein, we report a special case of pseudo-beta-hairpin formation by tetrapetide sequences featuring a two-membered Ant Pro dipeptide motif (Ant = anthranilic acid and Pro = proline) at the loop region. These folded structures uniquely feature the presence of C9- and C17-H-bonding patterns at reverse turn and interstrand regions, respectively. Their hairpin nucleation and folding propensities have been expounded using solution and solid state studies of distinct stereochemically altered sequences.

Heterogeneous foldamers from aliphatic-aromatic amino acid building blocks: current trends and future prospects - Nair, Roshna V.; Vijayadas, Kuruppanthara N.; Roy, Arup; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2014)
Chemists' constant pursuit of understanding of the underlying principles of nature's most intricate phenomenon such as protein folding has led to the development of the field of foldamers. The emergence of diverse classes of unnatural amino acid building blocks has unleashed countless opportunities to design, develop and explore the structural and functional aspects of synthetic peptides. One current trend in foldamer chemistry is the heterofoldamer approach, which involves systematic stoichiometric variation of various natural/unnatural amino acid residues, leading to conformational ordering with intriguing structural architectures. In this regard, the incorporation of aromatic amino acids provides efficient structural rigidification and tunability to the molecular scaffolds, which can exhibit a range of secondary structural features. Recent times have witnessed an upsurge of foldamers featuring aliphatic-aromatic residues with diverse structural propensities. This review is an effort to cover this rapidly developing field of foldamer science and also to envisage its future perspectives.
Keywords: Amino acids; Conformation analysis; Foldamers; hydrogen bonding; Peptides; Stacking interactions

Nucleophilic ring-opening of benzoxazinones by dbu: some observations - Baravkar, Sachin B.; Roy, Arup; Gawade, Rupesh L.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Synthetic Communications, 2014)
This communication demonstrates the formation of an unusual nucleophilic ring opening of benzoxazinones by 1,8-diazabicycloundec-7-ene (DBU). This observation contradicts the intrinsic feature of a hindered nonnucleophilic base like DBU. Confirmation of the product was achieved via single-crystal X-ray diffraction studies.
Keywords: Benzoxazinones; caprolactam; DBU; HATU

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.

Synthetic turn mimetics and hairpin nucleators: quo vadimus? - Nair, Roshna V.; Baravkar, Sachin B.; Ingole, Tukaram S.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
Structural mimicry of peptides has witnessed perceptible progress in the last three decades. Reverse turn and beta-hairpin units are the smallest secondary structural motifs that are some of the most scrutinized functional cores of peptides and proteins. The practice of mimicking, without altering the function of the bioactive core, ranges from conformational locking of the basic skeleton to total replacement of structural architecture using synthetic analogues. Development of heterogeneous backbones - using unnatural residues in place of natural ones - has broadened further opportunities for efficient structural rigidification. This feature article endeavours to trail the path of progress achieved hitherto and envisage the possibilities that lie ahead in the development of synthetic turn mimetics and hairpin nucleators.

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

Exploiting powder x-ray diffraction to establish the solvent-assisted solid-state supramolecular assembly of pillar[5]quinone - Shivakumar, Kilingaru I.; Yan, Yuncheng; Hughes, Colan E.; Apperley, David C.; Harris, Kenneth D. M.; Sanjayan, Gangadhar J. (Crystal Growth & Design, 2015)
We report the solvent-mediated supramolecular assembly of pillar[5]quinone (P[5]Q), a symmetric cyclamer containing five benzoquinone moieties bridged by five alternating methylene units. The supramolecular assembly of P[5]Q is shown to be facilitated by 1,1,2,2-tetrachloroethane (TCE) as solvent, producing a microcrystalline solvate material P[5]Q(.)2TCE with a fluffy texture. Optical and electron microscopy reveal that this material has a rod-shaped morphology, extending to several micrometers in length. Due to the microcrystalline nature of the material, structure determination was carried out directly from powder X-ray diffraction data, augmented by high-resolution solid-state C-13 NMR. The two crystallographically distinct TCE molecules occupy different types of void in the structure and have different dynamic properties. Crystallization of P[5]Q was attempted from a large number of different solvents, but only TCE was found to facilitate the formation of a crystalline phase. Indeed, features of the crystal structure suggest that the TCE component plays an important role in promoting the columnar assembly of P[5]Q molecules.

Novel hybrid nocodazole analogues as tubulin polymerization inhibitors and their antiproliferative activity - Kale, Sangram S.; Jedhe, Ganesh S.; Meshram, Sachin N.; Santra, Manas K.; Hamel, Ernest; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2015)
We describe the design, synthesis and SAR profiling of a series of novel combretastatin-nocodazole conjugates as potential anticancer agents. The thiophene ring in the nocodazole moiety was replaced by a substituted phenyl ring from the combretastatin moiety to design novel hybrid analogues. The hydroxyl group at the ortho position in compounds 2, 3 and 4 was used as the conformationally locking tool by anticipated six-membered hydrogen bonding. The bioactivity profiles of all compounds as tubulin polymerization inhibitors and as antiproliferative agents against the A-549 human lung cancer cell line were investigated Compounds 1 and 4 showed mu M IC50 values in both assays. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Anticancer; Colchicine; Nocodazole; Tubulin binding

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Role of N-terminal proline in stabilizing the Ant-Pro zipper motif - Kheria, Sanjeev; Nair, Roshna V.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2015)
Hetero-chiral hybrid peptides of the general sequence (L)alpha beta(D)(n)alpha beta(n) featuring proline (Pro, a constrained alpha-amino acid) and anthranilic acid (Ant, a constrained beta-amino acid) as building blocks, where n = 2, 4 etc., form a three-dimensional zipper-like architecture. These zipper peptides attain stable conformation by balancing the co-operative contribution of two competing non-covalent forces, namely hydrogen bonding and aromatic stacking. However, the selection of the N-terminal residue also stands to be one of the key contributors in stabilising the unusually long-range intramolecular hydrogen bond, featuring 26 atoms in the H-bonded ring observed at the termini. This article deals with the substitution alterations at the N-terminus of the zipper motif and their consequent influences on its structure and stability. In this study, the N-terminal Pro residue of the zipper motif was substituted with a flexible amino acid, alanine, and a constrained acyclic amino acid, 2-aminoisobutyric acid, to investigate the role of N-terminal proline in stabilizing the Ant-Pro zipper motif, and its stabilities were assessed by employing solution-state NMR and restrained MD simulation studies.

3-Aminothiophenecarboxylic acid (3-Atc)-induced folding in peptides - Ingole, Tukaram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2016)
This paper describes the consequences of incorporating a constrained heterocyclic aromatic b-amino acid 3-aminothiophenecarboxylic acid (3-Atc) into peptides containing beta-turn forming elements such as Pro-Gly motif and the effect on the secondary structural architecture of the entire peptide backbone. Conformational investigations of oligomers comprising an alpha,beta,alpha peptide sequence were carried out by single-crystal X-ray diffraction, solution-state NMR, nOe-restrained MD simulation and circular dichroism studies. The results suggested that these peptide sequences assume helical architecture. The helical folding in the oligomers was found to be devoid of inter-residual H-bonding, instead found to be stabilized by a co-operative effect of 6-membered H-bonding within the 3-Atc unit and conformational restrictions of individual amino acids in the peptide backbone.

Angiotensin II analogs comprised of pro-amb (gamma-turn scaffold) as angiotensin II type 2 (AT(2)) receptor agonists - Jedhe, Ganesh S.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Pasha, Santosh; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
We describe herein the design, synthesis and conformational investigation of Pro-Amb (proline-3-amino-2-methoxybenzoic acid) incorporated Angiotensin II and its truncated analogues. Solution-state NMR and CD studies suggest gamma-turn-like conformation in Pro-Amb analogs in aqueous solution. Furthermore, Pro-Amb analogs have been shown to act as AT(2) receptor agonists.

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Self-assembled vesicles of urea-tethered foldamers as hydrophobic drug carriers - Ingole, Tukaram S.; Kale, Sangram S.; Sukumaran, Santhosh Babu; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
Molecular self-assembly of nonamphiphilic alpha,beta-hybrid foldamers based on urea-tethered anthranilic acid-proline (Ant-Pro) foldamers is reported. These self-assembled hollow vesicular architectures can take up and release the anticancer hydrophobic drug curcumin.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Exploring the gem-dimethyl effect in the formation of imine-based macrocycles and cages - Madhu, Suresh; Rashmi, E. V.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2017)
Using the gem-dimethyl effect as a platform, a variety of organic [2+2] macrocycles and [2+3] cofacial cages was obtained in high yields. Imine-based macrocyclization could be performed even at high concentrations (0.5 to 1.0 M), via instant mixing of aldehydes and amines.

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Modular approach towards functionalized highly stable self-complementary quadruple hydrogen bonded systems - Rayavarapu, Suresh; Kheria, Sanjeev; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2017)
Self-complementary quadruple hydrogen bonded systems have shown potential as key building blocks for developing various supramolecular polymers. Opportunities for the introduction of multiple functionalities would further augment, in principle, their application potential. Herein, we report a novel modular approach to simultaneously introduce two closely aligned side chains into AADD-type self-complementary quadruple hydrogen-bonding systems. Dithiane-tethered ureidopyrimidinone has been used as a reactive intermediate to efficiently attach closely aligned side chains by simply reacting with amines to form highly stable molecular duplexes. These duplexes featuring AADD-type arrays of hydrogen bonding codes are highly stable in non-polar solvents (K-dim > 1.9 x 10(7) M-1 in CDCl3) as well as in polar solvents (K-dim > 10(5) in 10% DMSO-d(6)/CDCl3). Another notable feature of these self-assembling systems is their insensitivity to prototropy-related issues owing to their prototropic degeneracy, which will enhance their application potential in supramolecular chemistry.

Novel silaproline (Sip)-incorporated close structural mimics of potent antidepressant peptide drug rapastinel (GLYX-13) - Madica, Krishnaprasad; Nadimpally, Krishna Chaitanya; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2017)
Rapastinel (GLYX-13) is a C-amidated tetrapeptide drug under clinical development for adjunctive treatment of major depressive disorder (MDD). Rapastinel features two consecutive proline residues centered at the peptide sequence (Thr-Pro-Pro-Thr-NH2), which are detrimental to its biological activity. In this communication, we report the synthesis of very close structural analogues of rapastinel comprising silaproline (Sip) as proline surrogate. By virtue of its enhanced lipophilicity and metabolic stability, Sip introduction in the native rapastinel sequence is expected to improve its pharmacokinetic profiles.

Rigid peptide scaffold-incorporated structural analogs of the potent antidepressant peptide drug rapastinel (GLYX-13) - Nadimpally, Krishna Chaitanya; Chakrapani, Aswathi; Prabhu, Priyanka J.; Madica, Krishnaprasad; Sanjayan, Gangadhar J. (Chemistryselect, 2017)
Rapastinel (GLYX-13) is a natural amidated tetrapeptide (Thr-Pro-Pro-Thr-NH2)endowed with strong antidepressant property. Rapastinel shows considerable promise for treating drug-resistant major depressive disorder (MDD), and is under clinical phase III development. Herein, we report the synthesis of a novel class of analogues of the potent antidepressant peptide drug rapastinel featuring rigid dipeptide scaffolds comprising proline (L/D) and amino thiophene carboxylates (Atc). Amino thiophene carboxylate is a conformationally constrained aromatic beta-amino acid, known to rigidify peptide backbones thereby limiting the conformational flexibility of peptides and improving proteolytic stability.

Structural insights into the hydrogen-bonding and folding pattern in ant-ant-pro-gly tetrapeptides - Baravkar, Sachin B.; Kotmale, Amol S.; Mobin, Samir R.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2017)
In this paper, we provide structural insights into the hydrogen-bonding and folding pattern in Ant-Ant-Pro-Gly tetrapeptides (Ant: anthranilic acid; Pro: proline; and Gly: glycine). Comparison of the C-terminal esters and their amide analogs revealed strikingly different H-bonding networks. Whereas the ester analogs displayed an open structure without terminal H-bonding interactions, the amide analogs showed a completely folded structure. Structural details were revealed by using a combination of X-ray crystal structure studies and NOE-based molecular dynamics (MD) simulation studies.

Three in one: prototropy-free highly stable AADD-type self-complementary quadruple hydrogen-bonded molecular duplexes with built-in fluorophore - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Sanjayan, Gangadhar J. (Chemical Communications, 2017)
This communication reports an effective approach for addressing the prototropy-related problems in heterocycle-based AADD-type self-assembling systems by freezing their hydrogen-bonding codes, by utilizing intramolecular bifurcated hydrogen bonding interactions. Using this strategy, we have also developed a hydroquinone-conjugated AADD-type self-assembling system adorned with three valuable features such as prototropy-free dimerization yielding single duplexes, high duplex stability and a built-in fluorophore, which would augment its application potential. The rational approach used herein to arrest prototropic shift may also find application elsewhere, wherein proton shift-mediated structural changes become a detrimental factor.

Triazine-based highly stable AADD-type self-complementary quadruple hydrogen-bonded systems devoid of prototropy - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Chemistry-A European Journal, 2017)
A new class of 1,3,5-triazine-based quadruple hydrogen-bonded system featuring AADD-type self-complementary arrays has been developed and characterized. This system forms highly stable molecular duplex in non-polar solvent (K-dim > 1.9 x 10(7) M-1 in CDCl3) without prototropy-related issues, raising its prospects for application in supramolecular polymer science.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Helically structured peptide architecture engineered using dimedone as a rigid organic scaffold - Nadimpally, Krishna C.; Madica, Krishnaprasad; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
This communication reports the use of a rigid organic scaffold to attach two unsymmetrical peptide chains on a single carbon atom. The approach describes the step-by-step attachment of peptide chains to the rigid dimedone template (5,5-dimethyl-1,3-cyclohexanedione) - a molecular scaffold that directs orientation of the peptide helices in a well-defined arrangement via intra-molecular hydrogen bonding. The overall topology of the final molecules was studied using CD spectroscopy which suggested existence of helical architecture.

Synthesis and anticancer activity of conformationally constrained Smac mimetics containing pseudo beta turns - Baravkar, Sachin B.; Wagh, Mahendra A.; Paul, Debasish; Santra, Manas; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2018)
Herein, we report synthesis and in vitro anticancer activity of conformationally constrained Smac mimetics containing reverse turn inducing motifs "Ant-Pro" and "sAnt-Pro". The synthesis of Smac analogs with diverse hydrophobic groups at the C-terminus was carried out using solution phase peptide synthesis. The synthesis of Ant-Pro containing analogs 3a-j was carried out by ring opening of benzoxazinones 7a-c, whereas, their sulfonamide counterparts 4a-h were synthesized by using routine acid-amine coupling reaction. In vitro anticancer studies against breast cancer cell line MDA-MB-231 revealed that some of the new analogs had better anticancer activity than the standard AVPI Smac tetrapeptide. (C) 2018 Published by Elsevier Ltd.

Three-dimensional metal-organic polymer of multivalent hexaphenylbenzene - Madhu, Suresh; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Metal-Organic Frameworks(MOFs) synthesized from ligands more than ten co-ordinating sites may offer material applications due to their structural architecture. Herein, a synthesis of metal-organic framework is reported from a ligand featuring 12-aryl carboxylic acid groups appended on a hexaphenylbenzene and s-block element potassium. The synthesized MOF was characterized by thermogravimetric analysis, infrared spectroscopy and X-diffraction studies. The X-ray crystal structure of MOF was shown to have a significant number of trapped and coordinated water molecules in its three-dimensional framework.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template

Efficient and convenient route for the synthesis of thiophene-2-carboxamidines as potential inhibitors of nitric oxide synthase (NOS) - Rashid, P. P.; Singh, Dharmendra; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2019)
A mild and efficient synthesis of substituted thiophene-2-carboxamidines which are potent inhibitors of nitric oxide synthase (NOS) is reported herein. The key step involves reaction of a BOC-protected imidazolyl thiophene-2-carboxamidine reactive intermediate with various primary amines to form BOC-thio-phene-2-carboxamidines which could be readily deprotected using TFA to furnish free carboxamidines. The method is very mild and tolerates diverse substituents including sensitive peptide and amino acid fragments. This new methodology represents a substantial improvement to the literature method owing to its simplicity and hassle-free purification procedures. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Amidines; Nitric oxide synthase (NOS); Nitric oxide synthase inhibitors; Thiophene-2-carboxamidines

Novel cilengitide-based cyclic RGD peptides as alpha nu beta(3) integrin inhibitors - Meena, Chhuttan L.; Singh, Dharmendra; Weinmueller, Michael; Reichart, Florian; Dangi, Abha; Marelli, Udaya Kiran; Zahler, Stefan; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2020)
In this letter, we report a series of five new RGD-containing cyclic peptides as potent inhibitors to alpha nu beta(3) integrin protein. We have incorporated various unnatural lipophilic amino acids into the cyclic RGD framework of cilengitide, which is selective for alpha nu beta(3) integrin. All the newly synthesized cyclic peptides were evaluated in vitro solid phase binding assay and investigated for their binding behaviour towards integrin subtypes. All the cyclic peptides were synthesized in excellent yield following solution-phase coupling strategy. The cyclic RGD peptides 1a-e exhibited IC50 of 9.9, 5.5, 72, 11 and 3.3 nM, respectively, towards a alpha nu beta(3) integrin protein. This finding offers further opportunities for the introduction unusual amino acids into the cyclic peptide framework of cilengitide.
Keywords: Anticancer drugs; Cilengitide; Integrins; RGD cyclicpeptides

Three in one: triple G-C-T base-coded brahma nucleobase amino acid: synthesis, peptide formation, and structural features - Wagh, Mahendra A.; Maity, Rahul; Bhosale, Rohit J.; Semwal, Divyam; Tothadi, Srinu; Vaidhyanathan, Ramanathan; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This note reports the synthesis and peptide formation of a novel triple G-C-T nucleobase amino acid (NBA) building block featuring three recognition faces: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Readily obtainable in multigram scale in a remarkably easy one-step reaction, this unique NBA building block offers scope for wide ranging applications for nucleic acid recognition and nucleic acid peptide/protein interaction studies.

Triazine-based janus G-C nucleobase as a building block for self-assembly, peptide nucleic acids, and smart polymers - Meena, Chhuttan L.; Singh, Dharmendra; Kizhakeetil, Bhavya; Prasad, Manasa; George, Malini; Tothadi, Srinu; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This communication reports on the utility of a triazine-based self-assembling system, reminiscent of a Janus G-C nucleobase, as a building block for developing (1) supramolecular polymers, (2) peptide nucleic acids (PNAs), and (3) smart polymers. The strategically positioned self-complementary triple H-bonding arrays DDA and AAD facilitate efficient self-assembly, leading to a linear supramolecular polymer.

Janus cross-links in supramolecular networks - Mondal, Swagata; Lessard, Jacob J.; Meena, Chhuttan L.; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (Journal of the American Chemical Society, 2022)
Thermosets composed of cross-linked polymers demonstrate enhanced thermal, solvent, chemical, and dimensional stability as compared to their non-cross-linked counterparts. However, these often-desirable material properties typically come at the expense of reprocessability, recyclability, and healability. One solution to this challenge comes from the construction of polymers that are reversibly cross-linked. We relied on lessons from Nature to present supramolecular polymer networks comprised of cooperative Janus-faced hydrogen bonded cross-links. A triazine-based guanine-cytosine base (GCB) with two complementary faces capable of self-assembly through three hydrogen bonding sites was incorporated into poly(butyl acrylate) to create a reprocessable and recyclable network. Rheological experiments and dynamic mechanical analysis (DMA) were employed to investigate the flow behavior of copolymers with randomly distributed GCB units of varying incorporation. Our studies revealed that the cooperativity of multiple hydrogen bonding faces yields excellent network integrity evidenced by a rubbery plateau that spanned the widest temperature range yet reported for any supramolecular network. To verify that each Janus-faced motif engages in multiple cross-links, we studied the effects of local concentration of the incorporated GCB units within the polymer chain. Mechanical strength improved by colocalizing the GCB within a block copolymer morphology. This enhanced performance revealed that the number of effective cross-links in the network increased with the local concentration of hydrogen bonding units. Overall, this study demonstrates that cooperative noncovalent interactions introduced through Janus-faced hydrogen bonding moieties confers excellent network stability and predictable viscoelastic flow behavior in supramolecular networks.

Multi-purpose synthetic alpha-amino acid featuring coumarin and ureidopyrimidinone motifs on its backbone: Synthesis and peptide formation - Rashid, P. P.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2022)
Herein we report a synthetic a-amino acid featuring intensely fluorescent coumarin moiety and a strongly self-assembling ureidopyrimidinone (UPy) motif. This two-in-one synthetic amino acid, displaying both fluorescence and self-assembling property, has been synthesized in four easy steps starting from commercially available inexpensive starting materials. Suitably protected amino acid has been incorporated into various peptide sequences, following solution-phase peptide coupling protocols, to demonstrate its synthetic feasibility.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Fluorescent amino acids; Fluorescent Peptides; Quadruple hydrogen bonding; Unnatural amino acids; Ureidopyrimidinone

Carbamate-Protected (BOC and O-NB) 2-Aminopyrimidinedione-based janus G-C nucleobase motifs as building blocks for supramolecular assembly and smart polymers - Singh, Dharmendra; Lakshmi, Durga; Meena, Chhuttan L.; Krishna, Gamidi Rama; Sanjayan, Gangadhar J. (Journal of organic chemistry, 2023)
In this paper, we report ``carbamate protected'' 2-aminopyrimidinedione-based Janus G-C nucleobases (2-APD Janus G-C nucleobases) featuring polymerizable groups and self-complementary triple H-bonding motifs DDA and AAD as building blocks for developing smart polymers and self-healing materials. The carbamate-masked H-bonding motif, cleavable under acidic (BOC group) or photocleavable (O-nitrobenzyl group) conditions, would facilitate the synthesis of smart polymers by alleviating aggregation during polymerization which in turn would exclude self-assembly-assisted solubility issues. Ready accessibility in excellent yields coupled with the possibility for facile introduction of polymerizable groups would make these building blocks excellent candidates for diverse polymerization applications.

Discovery of SARS-CoV-2 inhibitors featuring novel histidine α-nitrile motif - Gone, Nilu Vijay; Enayathullah, Mohammed Ghalib; Thomas, Jessie; Rathee, Parth; Prabhakar, Rajeev; Bokara, Kiran Kumar; Sanjayan, Gangadhar J. (Chemistry and Biodiversity, 2023)
As COVID-19 infection caused severe public health concerns recently, the development of novel antivirals has become the need of the hour. Main protease (Mpro) has been an attractive target for antiviral drugs since it plays a vital role in polyprotein processing and virus maturation. Herein we report the discovery of a novel class of inhibitors against the SARS-CoV-2, bearing histidine alpha-nitrile motif embedded on a simple dipeptide framework. In-vitro and in-silico studies revealed that the histidine alpha-nitrile motif envisioned to target the Mpro contributes to the inhibitory activity. Among a series of dipeptides synthesized featuring this novel structural motif, some dipeptides displayed strong viral reduction (EC50=0.48 mu M) with a high selectivity index, SI>454.54. These compounds also exhibit strong binding energies in the range of -28.7 to -34.2 Kcal/mol. The simple dipeptide structural framework, amenable to quick structural variations, coupled with ease of synthesis from readily available commercial starting materials are the major attractive features of this novel class of SARS-CoV-2 inhibitors. The histidine alpha-nitrile dipeptides raise the hope of discovering potent drug candidates based on this motif to fight the dreaded SARS-CoV-2.
Keywords: dipeptide inhibitors; histidine alpha-nitrile; M-pro (main protease); molecular dynamics; SARS-CoV-2

Histidinal-based potent antimalarial agents - Meena, Chhuttan L.; Hingamire, Tejashri; Gupta, Tanya; Deshmukh, Bhagyashree; Karmodiya, Krishanpal; Joshi, Rakesh; Shanmugam, Dhanasekaran; Sanjayan, Gangadhar J. (ChemMedChem, 2023)
Herein we report the synthesis and evaluation of peptide-histidinal conjugated drug scaffolds, which have the potential to target the hemoglobin-degrading proteases falcipain-2/3 from the human malaria parasite. Scaffolds with various substitutions were tested for antimalarial activity, and compounds 8 g, 8 h, and 15 exhibited EC50 values of similar to 0.018 mu M, similar to 0.069 mu M, and similar to 0.02 mu M, respectively. Structure-based docking studies on falcipain-2/3 proteases (PDB:2GHU and PDB:3BWK) revealed that compounds 8 g, 8 h, and 15 interact strongly with binding sites of falcipain-2/3 in a substrate-like manner. In silico ADME studies revealed that the molecules of interest showed no or minimal violations of drug-likeness parameters. Further, phenotypic assays revealed that compound 8 g and its biotinylated version inhibit hemoglobin degradation in the parasite food vacuole. The identification of falcipain-2/3 targeting potent inhibitors of the malaria parasite can serve as a starting point for the development of lead compounds as future antimalarial drug candidates.
Keywords: artemisinin; chloroquine; digestive vacuole; docking; falcipains; falciparum; P

Block copolymer self-assembly: exploitation of hydrogen bonding for nanoparticle morphology control via incorporation of triazine based comonomers by RAFT polymerization - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; Kuchel, Rhiannon P.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Small, 2024)
Synthesis of polymeric nanoparticles of controlled non-spherical morphology is of profound interest for a wide variety of potential applications. Self-assembly of amphiphilic diblock copolymers is an attractive bottom-up approach to prepare such nanoparticles. In the present work, RAFT polymerization is employed to synthesize a variety of poly(N,N-dimethylacrylamide)-b-poly[butyl acrylate-stat-GCB] copolymers, where GCB represents vinyl monomer containing triazine based Janus guanine-cytosine nucleobase motifs featuring multiple hydrogen bonding arrays. Hydrogen bonding between the hydrophobic blocks exert significant influence on the morphology of the resulting nanoparticles self-assembled in water. The Janus feature of the GCB moieties makes it possible to use a single polymer type in self-assembly, unlike previous work exploiting, e.g., thymine-containing polymer and adenine-containing polymer. Moreover, the strength of the hydrogen bonding interactions enables use of a low molar fraction of GCB units, thereby rendering it possible to use the present approach for copolymers based on common vinyl monomers for the development of advanced nanomaterials.

Creep resistance in doubly crosslinked dynamic covalent networks - Mondal, Swagata; Wong, Alexander J.; Wagh, Mahendra A.; Alperstein, Lily; Sanjayan, Gangadhar J.; Sumerlin, Brent S. (POLYMER CHEMISTRY, 2024)
Vitrimers are a unique class of thermosets that demonstrate reprocessability and recyclability due to dynamic bond exchange at crosslinking sites. However, the same dynamic bond exchange predisposes vitrimers to macroscopic deformation and creep under constant stress, which limits many practical applications. Herein, we demonstrated that the incorporation of Janus-faced guanine-cytosine diamine (GCBDam) functionality within vinylogous urethane vitrimers leads to significant creep resistance due to network reinforcement via hydrogen bonding. The supramolecular associations of the GCBDam groups retarded stress relaxation at temperatures as high as 160 degrees C. Further, rheological data suggested that the cooperative nature of the bifunctional Janus-faced hydrogen bonding moieties allowed the GCBDam to act as ``stickers'' within the dynamic covalent networks. These results indicate that incorporating the bifunctional supramolecular moiety improved dimensional stability while conserving the hallmark vitrimer property of reprocessability. This work demonstrates that incorporating Janus-faced supramolecular moieties in vinylogous urethane vitrimers improved dimensional stability while conserving the hallmark vitrimer property of reprocessability.

Synthesis and film formation of aqueous emulsion polymer latexes featuring hydrogen bonding via a janus guanine-cytosine base monomer - Thompson, Steven W.; Li, Joanna; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (ACS APPLIED POLYMER MATERIALS, 2024)
Keywords: Emulsion polymerization; Film formation; Hydrogenbonding; Supramolecular networks

Morphology rearrangement by mixing of internally hydrogen-bonded nanoparticles comprising triazine-based amphiphilic diblock copolymers - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; van der Tol, Joost J. B.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Macromolecules, 2025)
The self-assembly of block copolymers holds significant potential for designing functional nanoparticles in materials science, nanomedicine, and nanotechnology. While the self-assembly of amphiphilic diblock copolymers is relatively well understood, the influence of specific supramolecular interactions, particularly hydrogen bonding, in directing their morphological behavior remains largely unexplored. In this study, it was demonstrated that nanoparticles self-assembled in water/DMSO (75/25 vol/vol; 2 mg/mL) comprising amphiphilic diblock copolymers with a small amount of triazine-based guanine-cytosine (GCB) motifs incorporated in the hydrophobic block can undergo spontaneous rearrangement into new morphologies on mixing. For example, mixing spheres with vesicles resulted in spontaneous transformation into worms (nanofibers), and this transformation was accelerated at elevated temperature. The hydrogen bonding motif features three complementary hydrogen bonding sites on either side of the nucleobase unit, thereby having a Janus character. Amphiphilic diblock copolymers comprising dimethyl acrylamide (hydrophilic segment) and n-butyl acrylate (hydrophobic segment) were synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization with a variable content of acrylate monomer functionalized with the Boc-protected form of the GCB motif as part of the hydrophobic segment. The present work represents a completely new approach for controlling self-assembly processes, paving the way for the design of functional nanoparticles for a range of applications.

Triple G-C-T base-coded self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications - Singh, Dharmendra; Gone, Nilu V.; Bandi, Kiran; Davis, Disiya; Nair, Kiran Sukumaran; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2025)
We report self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications. These nucleobase monomers are adorned with nature-inspired triple G-C-T nucleobases featuring three recognition sites: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Using readily accessible starting materials, these monomers can be synthesized in excellent yields, making them good choices for diverse applications. Their unique structural features, coupled with their water solubility, may offer exciting opportunities for the creation of new biomaterials.

Dynamic janus hydrogen bond mimicry unlocks tough, flexible supramolecular elastomers for strain sensing - Lakshmi, Durga; Wagh, Mahendra A.; Sharma, Aakash; Alam, Md Shafi; Selvan, T. Muthamil; Torris, Arun; Mondal, Titash; Sanjayan, Gangadhar J.; Nair, Kiran Sukumaran (Chemistry of Materials, 2026)
Flexible and wearable electronics demand stretchable sensors with polymer elastomers as key matrixes for mechanical flexibility and durability. However, despite their excellent elasticity, their limited mechanical strength remains a challenge. To address this limitation, in this study, we report the rational design of supramolecular polyurethane elastomers (SPUs) incorporating nucleobase-inspired aminopyrimidinedione with DDA-AAD (G-C mimic) reversible triple hydrogen bonds. This dual-domain architecture gives rise to a durable supramolecular network with enhanced mechanical properties, yielding elastomers that are soft, stretchable, and tough. By tuning of the density of dynamic cross-links, mechanical properties were systematically modulated. SPU-0.5 exhibited a maximum tensile strength of 16.14 MPa, representing a 67-fold strength enhancement over that of SPU-0. Although increasing the aminopyrimidinedione (APD) content reduced elongation, SPU-0.2 retained a high elongation of 1060% and showed the lowest residual strain during cyclic tests. To be of great interest, the activation energy increased with increasing hydrogen bonding content up to SPU-0.1, whereas beyond SPU-0.2 it decreased, likely due to extensive hydrogen bond formation. Furthermore, SPU-0.2-SP, a conductive variant, demonstrated a promising strain-sensing performance even after hundreds of cycles. Overall, the insights gained from this study advance the development of intelligent soft materials and lay the groundwork for next-generation flexible and wearable electronic devices.

Repurposed ciprofloxacin derivatives as potent autophagic-type anticancer agents - Gone, Nilu Vijay; Sharma, Tanisha; Joshi, Rakesh; Upreti, Akshita; Santra, Manas; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2026)
Drug repurposing - also known as drug repositioning is a proven strategy for identifying new therapeutic uses for existing and pre-approved drugs with considerable success in recent years. Herein, we report the discovery of a novel class of ciprofloxacin-amino acid conjugates that are dynamically potent against different cancer cell lines. Some of the molecules reported herein displayed a strong anti-proliferative effect on MCF-7 (IC50: 6 mu M). The most active anti-proliferative molecule of this series 7a suppressed the proliferation of HCT116, A549, and MDAMB-231 cancer cell lines. Furthermore, we established that the treatment with 7a leads to DNA damage-mediated autophagic cell death in cancer cells. Our findings suggest that appropriate derivatization of the ciprofloxacin drug can yield promising anti-cancer compounds in easy synthetic operations.
Keywords: Anticancer drugs; Autophagic cell death; ciprofloxacin